Mastering InDesign CS5 for print design and production - Burke, Pariah S. (Serious skills., 2011)
"Comprehensive reference and tutorial on Adobe InDesign CS5 If you want to thoroughly master InDesign from the basics through advanced topics, Mastering InDesign CS5 for Print Design and Production is the book you need. Written by the former InDesign technical lead for Adobe, this book helps you achieve professional results through efficient production workflows and advanced techniques. You'll learn how to collaborate within workgroups; work efficiently with text, objects, and variable text; perfect your printed output; get the most out of InDesign's transparency and effects tools, and much more. Above all, you'll see how to handle prepress to get the results you want. Shows you how to use Adobe InDesign CS5 to achieve professional results Written by the former InDesign technical lead for Adobe, who, in addition to his technical expertise, offers his own valuable advice and lessons learned from 20 years in the graphic design business Offers comprehensive coverage of topics, step-by-step instruction, and numerous examples and case studies Whether you're just starting with InDesign or a professional using it every day, this comprehensive guide will take your skills to a new level"--